PENGARUH PERKEMBANGAN TEKNOLOGI INFORMASI TERHADAP BIDANG AKUNTANSI MANAJEMEN - Putri Alea; Andina Suci Ariyani; Sabrina Ayu Kamalia; Alfiyatur Rosyidah; Syifa Salsa Rahmadhani; Husni Mubarok (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study examines the effect of information technology (IT) development on the field of management accounting through a literature study approach to eight major scientific sources published in the range 2021–2026. The purpose of this study is to outline how IT is changing the role of management accountants, identify new competencies required in the digital age, and explain the positive impact, challenges, and risks of implementing IT in management accounting. The results show that IT development has shifted the role of management accountants from administrative functions and routine recording to a strategic role as a data-based strategic recommendation provider actively involved in decision-making. Systems such as ERP, cloud accounting, artificial intelligence (AI), and big data analytics have been shown to improve operational efficiency, data accuracy, and the quality of information produced. In addition to these benefits, IT implementation also presents challenges in the form of gaps in human resources digital competency, data security risks, algorithmic bias, and high infrastructure investment costs. These findings assert that the success of digital transformation in management accounting depends on the synergy between technology mastery, data analytics capabilities, and adaptive organizational culture.